ESL Students’ Learning Strategies for the Improvement of their Language Skills - Irwandi Irwandi; Muhammad Hudri; Dina Apriana (Muhammadiyah University of Mataram, 2022)
Effective language strategies contribute to learners’ success in learning English. In relation to this, this study aims at investigating ESL students’ strategies in learning a language. Those strategies are metacognitive strategies, deep cognitive strategies, and surface cognitive strategies. 50 English department students participated in a survey that required them to reflect on their own learning strategies for the four language skills by answering 80 questions. The result of the study suggests that the metacognitive strategies are the most highly used to improve their language skills compared to the deep cognitive and surface cognitive strategies that are moderately used. The data also showed those strategies are widely used in written texts insteadof spoken texts.